A Crisis of Governance: Zimbabwe - Jacob Chikuhwa (Algora, 2004)
This is a detailed analysis of Zimbabwe's struggle to become a viable independent state, with a focus on the tumultuous events under President Robert Mugabe. Problems range from the need for constitutional reform to political patronage and a de facto one-party democracy and the need for transparency in land reform, privatization, and economic liberalization. It is one thing to break free of colonial tutelage; it is quite another to recover from the legacy of colonialism and implement the macroeconomic changes that would lay the basis for a self-sustaining economy. The crisis of governance in Zimbabwe (formerly known as Rhodesia) began with the occupation of Mashonaland by the British South Africa Company (BSAC) in 1890. Self-rule and the subsequent British-sponsored constitutions did not much improve the situation, and the 1965 Unilateral Declaration of Independence only aggravated it.